Absorption of Heavy Metal Mercury (Hg) in Long Bean (Vigna unguiculata L. Walp) with Variation of Planting Period and Planting Medium - Anggy ulul Ningtyas; Suhadi Suhadi; Agus Dharmawan (Jurnal Ilmu Hayat, 2021)
The amalgamation technique of Sekotong gold mining produces heavy metal pollution in agricultural areas. The purpose in this study to find the effect of mine soil variations on growing media on growth and absorption of mercury in long bean (V. unguiculata L. Walp). This experimental study uses RCBD with a mixture of katel soil and mine soil media A (100% katel soil), B (80%: 20%), C (60%: 40%), D (40%: 60%) and E (20%: 80%) and 5 replications. Data collection on growth of stem height and number of leaves every week while the absorption of mercury every 1, 2, 3 and 4 months of planting. Data analyzed with One Way Anova test, Mann Whitney test and T-test. Results of analysis showed effect of variation in planting media on stems height and number of leaves from highest to lowest is media A, B, C were significantly different, followed D and E not significantly different. Mercury absorption of media A and C roots, stems, leaves, fruits 1 and 4 months of planting significantly different, not significantly different from root 2 months of planting and roots, stems and fruits 3 months of planting. Total absorption of mercury media A and C was significantly different.